Citizen Journalism and Democratisation of Mainstream Media in Rwanda. Issue 2 (3rd April 2017) - Nduhura, Dominique; Prieler, Michael
ABSTRACT: This paper explores the role that citizen journalism is playing in democratising the mainstream media in Rwanda. Through in-depth interviews with journalists from two radio stations and by using the public sphere theory as a theoretical framework, this research sought to answer the question as to whether citizen journalism in Rwanda propels media democratisation by enabling democratic deliberation through its ability to inform, filling in the gaps left by mainstream media and by encouraging critical thinking. The findings from this study show that citizens participate in the daily work of the media through commentaries and by serving as news sources. However, citizens have not yet had a tangible impact on the functioning of the two media where self-censorship and gatekeeping are widely practised. Democratisation of these radio stations appears to be more theoretical rather than an established practice. Hence, the public sphere in the Habermasian sense is not yet a reality.